2016
DOI: 10.1098/rspb.2016.1562
|View full text |Cite|
|
Sign up to set email alerts
|

Population differences in olfaction accompany host shift in Drosophila mojavensis

Abstract: Evolutionary shifts in plant -herbivore interactions provide a model for understanding the link among the evolution of behaviour, ecological specialization and incipient speciation. Drosophila mojavensis uses different host cacti across its range, and volatile chemicals emitted by the host are the primary cue for host plant identification. In this study, we show that changes in host plant use between distinct D. mojavensis populations are accompanied by changes in the olfactory system. Specifically, we observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 46 publications
4
47
0
Order By: Relevance
“…Second, Mojave population females, in particular, had marked preferences for their own host plant, barrel cactus, when given a choice of it versus an alternative. This result is consistent with past research, suggesting that the Mojave population diverged with host shift in its genetic structure, olfactory electrophysiological and behavioral responses to cactus volatiles (Ross & Markow, ; Date et al., ; Crowley‐Gall et al., ). Finally, it is interesting that the mainland Sonoran population prefers its host, organ pipe cactus, but only when paired with barrel.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Second, Mojave population females, in particular, had marked preferences for their own host plant, barrel cactus, when given a choice of it versus an alternative. This result is consistent with past research, suggesting that the Mojave population diverged with host shift in its genetic structure, olfactory electrophysiological and behavioral responses to cactus volatiles (Ross & Markow, ; Date et al., ; Crowley‐Gall et al., ). Finally, it is interesting that the mainland Sonoran population prefers its host, organ pipe cactus, but only when paired with barrel.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, a synthetic mixture of barrel volatiles was shown to preferentially attract flies from the Mojave population (Date et al, 2013). Population differences in olfactory sensory neuron number, sensitivity, and specificity have also been observed in this system (Crowley-Gall et al, 2016).…”
mentioning
confidence: 85%
“…For example, a comparison of D. melanogaster and Drosophila sechellia , a specialist that oviposits only on morinda fruit, revealed that D. sechellia shows enhanced attraction to a subset of morinda-derived odorants and increased abundance of the antennal neurons that respond to these odorants (Dekker et al 2006). Similar changes have been observed for other Drosophila species, mosquitos, and bees (Burger et al 2013; Crowley-Gall et al 2016; Linz et al 2013; Syed and Leal 2009). In addition to showing enhanced responses to odorants emitted by their food sources or oviposition substrates, some specialists also show reduced responses to odorants emitted by other sources.…”
Section: Discussionsupporting
confidence: 84%
“…; Crowley‐Gall et al. ) despite much shorter divergence times than between H. melpomene and H. cydno (approximately 2.1 million years ago; Arias et al. ; Kozak et al.…”
Section: Discussionmentioning
confidence: 99%